2021
DOI: 10.1016/j.jmig.2021.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcomes Following Surgical Management for Isthmoceles: A Systematic Review

Abstract: Objective: To evaluate the efficacy of surgical management for isthmoceles in patients presenting with secondary infertility. Data Sources: A systematic search was performed in MEDLINE, EMBASE, and Cochrane Library databases from inception to May 2020. The search was limited to studies published in English. Methods of Study Selection: After the removal of duplicates, 3380 articles were screened for inclusion independently by 2 authors. These 2 authors assessed for studies which focused on women of reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Second, Harjee et al ( 44) published a systematic review on reproductive outcomes after surgical management for uterine niches. The investigators concluded that the surgical treatment of niches, particular through hysteroscopy in patients with a residual myometrium of at least 2.5 mm, may be effective in treating niche-associated infertility (44).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Second, Harjee et al ( 44) published a systematic review on reproductive outcomes after surgical management for uterine niches. The investigators concluded that the surgical treatment of niches, particular through hysteroscopy in patients with a residual myometrium of at least 2.5 mm, may be effective in treating niche-associated infertility (44).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Our systematic review differs from both publications on a number of points. Compared with Harjee et al (44), we included 7 additional articles published in the last year about women with infertility with a niche (n ¼ 418 women). Second, we also included 237 women without infertility.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…We have read with great interest the systematic review written by Harjee et al about reproductive outcomes following surgical management for isthmoceles (1). We embrace the awareness for longterm effects of caesarean sections, in particular with respect to the potential detrimental effect of isthmoceles on reproductive outcomes (2).…”
Section: To the Editormentioning
confidence: 99%
“…3 A deeper and larger fluid-filled triangular pouch at the isthmus is an isthmocele. 4 The prevalence and risk factors of isthmoceles are variable depending on detection methods and study populations. 2,5,6 Hysteroscopy allows diagnostic and minimally invasive surgical therapeutic approaches to isthmoceles.…”
Section: Introductionmentioning
confidence: 99%